Identifying Touchpoints for Foreign Tourists in the Customer Journey through 5 A's Approach - Mostafa Esmaeili Mahyari; Mohammad Ghaffari; Hamid Reza Irani; Elham Ebrahimi (‫مدیریت بازرگانی)
ObjectiveThe notions of customer journey and touchpoints are now fundamental in the realm of marketing, especially in the context of customer experience. The customer journey is comprised of three stages: pre-purchase, during purchase, and post-purchase, with numerous touchpoints where multiple stakeholders may shape the customer experience at each stage. Within the tourism industry, analyzing and identifying the touchpoints of tourists throughout their customer journey can aid destination managers and businesses in developing a meaningful and enduring experience for tourists. The 5A model provides an analytical framework to examine the customer experience during the customer journey, encompassing the steps of Awareness, Appeal, Ask, Act, and Advocacy. Thus, the purpose of this study is to utilize the 5A model to identify and investigate key touchpoints of tourists visiting Iran. MethodologyThe study employed an abductive research method, utilizing convenient and snowball sampling methods to select foreign tourists who have visited Iran in the last four years as participants. Data was collected through in-depth interviews, allowing participants to share their experiences, which were then subjected to thematic analysis. This involved repeated examination of the interviews, coding similar statements, and categorizing them into sub-themes, which ultimately yielded 23 themes that were further grouped into five overarching themes: awareness, appeal, ask, act, and advocacy. FindingsThe research revealed a total of 23 sub-themes, which were grouped into five distinct stages. These stages include the Awareness stage, which involves communication networks with Iranians, positive recommendations from friends and other tourists, literary sources, news media, and personal nostalgia. In the Appeal stage, factors such as being unknown compared to other countries of the world, the direct experience of history, the attractiveness of communication with the people, the food and customs of Iran, and the affordability of traveling to Iran come into play. The Ask stage incorporates experiences of experienced friends, tourist information on social media, international sites and books, and contact with travel agencies and Iranian-generated content on social media. Moving on to the Act stage involves the desire for immediate and individual experience, living an Iranian life, and discovering cultural and historical beauties. Finally, in the Advocacy stage, aspects like recommendation, defending against negative comments, willingness to revisit, bringing others in next travels, content creation on social media, and caring about Iran news play a role. ConclusionDuring all phases of a customer's journey, with particular emphasis on the Awareness and Ask stages, it is imperative to engage in advertising, content creation, and social media presence. The effectiveness of these efforts has a significant influence on tourists' cognizance and consequential decision-making concerning their destination selection. Furthermore, the results indicate that despite the use of technology and innovative service delivery practices, it is crucial to preserve authenticity and prioritize distinctive attractions and authentic experiences. Additionally, brand advocates active on social media platforms play a critical role in influencing potential tourists' decisions to travel to Iran by sharing their experiences and reacting to negative reviews.